DIRECT FACETING IN COMPOSITE RESIN AS AN AESTHETIC SOLUTION FOR RESTORING SMILE HARMONY - CASE REPORT - Fernandes, Gabriela Araujo; Santana, Ana Júlia Silva Rocha de; Rezende, Gustavo Henrique; Vilela, Ana Giulia; Rodrigues, Ana Laura Alves; Magalhães, Vitor Lucas Rezende; Port, Ana Clara; Sousa, Anna Beatriz de; Borges, Daniela; Melo, Maria Eduarda Soares e; et al. (CIPEEX, 2025)
The concept of aesthetics is associated with beauty, which integrates the specific shape, contour, texture, and color of each individual. The demands of contemporary society have led to a significant increase in the search for aesthetic treatments. The role of the dental surgeon is of great importance in this context, as the subjectivity of well-being also relates to social, psychological, and cultural factors. Objective: To report the clinical case of a patient who presented direct veneers on three anterior superior teeth that were unsatisfactory in terms of color and shape. After studying the clinical case, direct veneers with composite resin were indicated to restore the aesthetics of the teeth. Case report: The patient, ERRT, female, attended the UniEVANGÉLICA Dental Clinic complaining of “very ugly front teeth with yellow restorations.” The radiographic examination showed satisfactory endodontic treatment in tooth 12, with no periapical lesions. After planning the case, standard cavity preparation for veneers was performed during the restorative session, removing the unsatisfactory restorations. The restorative protocol was followed: modified absolute isolation with cyanoacrylate, acid conditioning, application of primer/adhesive, accommodation of resin layers, and light curing until the appropriate contour with vestibular convexity was achieved. In the next session, the final finishing and polishing of the composite resins were performed. Conclusions: The direct technique with composite resin is accessible and versatile, proving to be an excellent option for performing aesthetic corrections quickly, with excellent cost-benefit, clinical longevity, and ease of repair when necessary.